Stresses Relaxation Mechanism in the Si-SiO2 System and its Influence on the Interface Properties (Global Journal of Science Frontier Research, 2017)
The results of the investigation of stresses relaxation by strain by means of EPR spectra, IR absorption spectra, SEM and samples deflection are presented. It has been shown that stresses relaxation mechanism depended on the oxidation condition: temperature, cooling rate, oxide thickness. In the Si-SiO 2 -Si 3 N 4 system the stresses relaxation by the strain occur due to the opposite sign of the thermal expansion coefficient of Si-SiO 2 and Si 3 N 4 on Si. Laser irradiation allows to modify the system stresses.
Keywords: Si-SiO2 interface; stress relaxation; EPR; SEM